Handbook on the study of multiple perpetrator rape : a multidisciplinary response to an international problem - Horvath, Miranda; Woodhams, Jessica (Taylor and Francis, 2013)
Whilst there is considerable literature on rape from various perspectives, there is very little that focuses on rape committed by multiple perpetrators (also referred to as group or gang rape). For the first time, this handbook brings together international multi-disciplinary perspectives on multiple perpetrator rape. The book is organised to provide readers with a comprehensive account of the thinking, theorising and empirical evidence on multiple perpetrator rape to date. Aspects covered include: different contexts in which multiple perpetrator rape occurs such as gangs, war.